EXPLORATION OF SEA CUCUMBER INTESTINAL SYMBIONT MICROBE AS PROBIOTIC MICROBE CANDIDATE IN HEALTHCARE PRODUCTS - Pringgenies, Delianis; Girsang, Putri Hutari; Yudiati, Ervia; Santosa, Gunawan Widi (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2020)
Natural ingredients from animals and plants generally have potential in pharmaceutical applications. However, there are still relatively little exploration made on the active ingredients from marine life. Sea cucumbers inhabit seabed and are filter feeders, consuming all microorganisms within their vicinity, which opens the prospect of medicinal applications of sea cucumber intestinal symbiont microbes. This study aims to obtain sea cucumber intestinal symbiont microbes with potential pharmaceutical application as probiotic microbe candidate. The study was carried out by collecting samples, microbe isolation, antimicrobial screening, identification of potential probiotic microbe candidate. Characteristics of the microbe were studied by biochemical screening, and molecular identification. The study found 21 microbial isolates from Holothuria atra and 30 microbial isolates from Holothuria leucospilota. Antimicrobial activity screening results against pathogens of Bacillus cereus dan Pseudomonas aeruginosa found 13 microbial isolates with positive activity. Four species were identified by molecular identification, namely Bacillus aquimaris, Bacillus maritimus, Bacillus toyonensis, and Virgibacillus chiguensis, whereas the other nine were identified by biochemical screening. Four microbe genus, namely Rothia sp., Listeria sp., Micrococcus sp., and Staphylococcus sp, were found to be the most viable candidate for probiotics. It was concluded that Bacillus sp., Rothia sp., Micrococcus sp., and Staphylococcus sp. Exhibited the most potential as probiotic microbes.